2022
DOI: 10.7759/cureus.22421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnetic Resonance Imaging With Axial Traction of the Thumb Carpometacarpal Joint on Articular Cartilage Visibility: A Feasibility Study

Abstract: The objective of this study was to verify the usefulness of magnetic resonance imaging (MRI) with axial traction of the thumb for observing articular cartilage. Materials and methodsEleven healthy adult volunteers (39.7 ± 7.4 years) without thumb carpometacarpal joint arthritis or trauma were included in this study. A 3-tesla (3T) MRI (Magnetom Skyra, Siemens Healthineers AG, Munich, Germany) of the right thumb with axial traction applied by a finger trap with three traction weights (0, 2, and 5 kg) was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…The MRI was initially performed without traction (no weight was used), followed by an MRI with traction. A traction weight of 3 kg was used based on our previous research [16].…”
Section: Image Acquisitionmentioning
confidence: 99%
See 3 more Smart Citations
“…The MRI was initially performed without traction (no weight was used), followed by an MRI with traction. A traction weight of 3 kg was used based on our previous research [16].…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Joint space width was measured on sagittal and coronal images at the center of the proximal articular surface of the first metacarpal bone as previously described [16]. On the sagittal image, the AB line, the line through both the volar (point A) and dorsal (point B) borders at the proximal articular surface of the first metacarpal bone; and the CD line, the line through both the volar (point C) and dorsal (point D) borders of the distal articular surface of the trapezium were drawn first.…”
Section: Measurement Of the Joint Space Widthmentioning
confidence: 99%
See 2 more Smart Citations
“…More evidence is required to determine the ideal traction weight for traction MRI of the elbow. Recent studies have applied axial traction to the thumb carpometacarpal joint [ 14 ], knee [ 15 ], and shoulder [ 16 ]. These studies found 5 kg of axial traction to be safe and sufficient for visualizing the thumb carpometacarpal joint and knee articular cartilage without arthrography, whereas 4 kg was sufficient to demonstrate morphological changes in the shoulder.…”
Section: Introductionmentioning
confidence: 99%